Writing STEAM : Composition, STEM, and a New Humanities. - Kao, Vivian; Kiernan, Julia, 1980- ([Place of publication not identified] : Routledge, 2022)
This edited collection positions writing at the center of interdisciplinary higher education, and explores how writing instruction, writing scholarship, and writing program administration bring STEM and the humanities together in meaningful, creative, and beneficial ways. Writing professionals are at the forefront of a cross-pollination between STEM (Science, Technology, Engineering, and Mathematics) and the arts and humanities. In their work as educators, scholars, and administrators, they collaborate with colleagues in engineering, scientific, technical, and health disciplines; offer new degree programs that allow students to bring the humanities to bear on design experiments, and build an academic culture that promotes a vision of the humanities in the twenty-first century, as well as a vision of technology that is decidedly human. This collection surveys and promotes that work through chapters focused on instruction, scholarship, and writing program administration, covering topics that include data-driven writing courses, public science communication, non-traditional college students, creative writing, gamification, skills transfer, and Writing Across the Curriculum programs. Writing STEAM will be essential reading for scholars, instructors, and administrators in writing studies, rhetoric and composition, STEM, and a variety of interdisciplinary programs; it will aid in teacher training for both humanities and STEM courses focused on writing and communication.
IntroductionVivian Kao and Julia E. KiernanSection I. TeachingChapter 1. Gaining STEAM: The Integral Role of Composition in an Increasingly STEM WorldKatelynn DeLucaChapter 2. Building Socioscientific Trust is a Post-Secondary Obligation: Preparing STEM Students to Communicate and Engage with Public AudiencesJulia E. KiernanChapter 3. STEAM Storytime: Fusing Artistic Expression with Scientific Discourse through Picture BooksRebekah Fitzsimmons & Tamara PearsonChapter 4. Interdisciplinary Collaboration for a New Humanities and a New EngineerOlivia Burgess & Alina HandoreanSection II. Research and ScholarshipChapter 5. STEAMing Up Composition: Inquiry-Based Learning and the Non-Traditional StudentErica Duran & Lauren Mecucci SpringerChapter 6. Knowledge in the Making: How STEAM can Transform Notions of ExpertiseRolf NorgaardChapter 7. Toward a Mindful Application of GamificationWhitney HardinChapter 8. Familiar Technologies and Learning Principles to Attract and Retain STEM Student Interest in First-Year WritingJohn MisakChapter 9. Creative Writing Across the Curriculum: Defining and Illustrating a Method for STEM/Humanities IntegrationJustin NicholesSection III. Writing Program AdministrationChapter 10. "Some of the rooms are occupied by squirrels": Communication and the New PolytechnicSarah V. SeeleyChapter 11. All Aboard: Gaining STEAM in Health Sciences EducationCourtney WatsonChapter 12. "To Feel, With Amazement, Their Minds": Science, Humanism, Inquiry, and the Rhetorical Work of WonderKara WittmanChapter 13. Local Exigencies in a World of Expectations: STEM Writing Programs and the Great Balancing ActVivian Kao, Aviva Gordon, Daniel Moyer, & Abir Sleiman
Keywords: English language -- Rhetoric